Reconsidering the Date and Provenance of the Book of Hosea: The Case for Persian-Period Yehud - Bos, James M. (The Library of Hebrew Bible / Old Testament Studies, 2013)
Scholarship has viewed the book of Hosea as originating in eighth-century Israel before being taken to Judah, where it underwent one or more redactions in later centuries. However, evidence suggests that the book should be viewed as a Judahite text from the start, of late sixth or early fifth century B.C.E composition. The post-monarchic period in Yehud provides the most fitting context for the anti-monarchical ideology of the book, with the polemic against Benjamin explicable only as a result of the tension between the governing Saulides resident in Mizpah and the Judahite elite who had recen